If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(n+3)+2(n+3)=3
We move all terms to the left:
(n+3)+2(n+3)-(3)=0
We multiply parentheses
(n+3)+2n+6-3=0
We get rid of parentheses
n+2n+3+6-3=0
We add all the numbers together, and all the variables
3n+6=0
We move all terms containing n to the left, all other terms to the right
3n=-6
n=-6/3
n=-2
| 5(3x+9)-2x=15x-2)x-5) | | -4r-5r=30 | | 6(3x+9)-2x=15x-2(x-5) | | 28+7x=20+1x | | 5×+4y=160 | | 9=3(5x2) | | 8x-3x+6=5x-2 | | 2.5k=30+k | | 8x-3x+6=5x-3 | | 4(2x4)-2x=6x+8 | | r^2-4r-62=0 | | 5x2+30x+14=2-2x. | | N+3=2n-15 | | 2(5x-2)=8x+8* | | 5s*7=105 | | 3x-108=180 | | -5j-3=1 | | 4^5x-2=9 | | a18=3362,a38=7362 | | 82x-9=180 | | 2m-6+2=14 | | 3x-6=-2x=9 | | 14x-8-7x=2(4x-8)+8 | | 85-y=40 | | 5x+25x+5=25 | | 9(2x-3)=12×+4+6x | | 25+p-3=30 | | 3a+5×2=a | | n/4-31/4=2 | | Y=7x=-5 | | 21.1=21.1+y | | 6n-14=88 |